Examining the association between neuropsychiatric symptoms among people with dementia and caregiver mental health: are caregiver burden and affiliate stigma mediators? - Yi‐Jung Chen; Jian‐An Su; Jung‐Sheng Chen; Chieh-Hsiu Liu; Mark D. Griffiths; Hsin‐Chi Tsai; Chih‐Cheng Chang; Chung‐Ying Lin (2023)
Neuropsychiatric disturbances are common manifestations of dementia disorders and are associated with caregiver burden and affiliate stigma. The present study investigated affiliate stigma and caregiver burden as mediators for the association between neuropsychiatric symptoms of people with dementia (PWD) and caregiver mental health such as depression and anxiety.A cross-sectional survey study was carried out with 261 dyads of PWD and informal caregivers from the outpatient department of a general hospital in Taiwan. The survey included the Caregiver Burden Inventory (CBI), the Affiliate Stigma Scale (ASS), the Taiwanese Depression Questionnaire (TPQ), and the Beck Anxiety Inventory (BAI). Mediation models were tested using the Hayes' PROCESS macro (Model 4 for parallel mediation model; Model 6 for sequentially mediation model).Caregiver burden, affiliate stigma, caregiver depression, and caregiver anxiety were significantly associated with neuropsychiatric symptoms. After controlling for several potentially confounding variables, it was found that PWD's neuropsychiatric symptoms, caregiver burden and affiliate stigma significantly explained 52.34% of the variance in caregiver depression and 37.72% of the variance in caregiver anxiety. The parallel mediation model indicated a significantly indirect path from PWD's neuropsychiatric symptoms to caregiver mental health through caregiver burden and affiliate stigma, while the direct effect was not significant. Moreover, there was a directional association between caregiver burden and affiliate stigma in the sequential mediation model.These findings show that it is imperative to improve caregivers' perception of those with dementia to reduce internalized stigma and to improve caregivers' mental health. Implementation of affiliate stigma assessment in clinical practice would allow distinctions to be made between the impact of affiliate stigma and the consequences of caregiver burden to help inform appropriate intervention.